2008
DOI: 10.4049/jimmunol.180.2.727
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Acts Directly on Bone Marrow Myeloid Progenitors to Differentially Regulate GM-CSF or Flt3 Ligand-Mediated Dendritic Cell Differentiation

Abstract: Estrogen receptor (ER) ligands modulate hemopoiesis and immunity in the normal state, during autoimmunity, and after infection or trauma. Dendritic cells (DC) are critical for initiation of innate and adaptive immune responses. We demonstrate, using cytokine-driven culture models of DC differentiation, that 17-β-estradiol exerts opposing effects on differentiation mediated by GM-CSF and Flt3 ligand, the two cytokines that regulate DC differentiation in vivo. We also show that estradiol acts on the same highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
115
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(119 citation statements)
references
References 79 publications
3
115
0
1
Order By: Relevance
“…The same group noticed that ERa-mediated signaling is required for optimal dendritic cell function as assessed by MHC-II and CD86 expression and pro-inflammatory cytokine production (IL6 and IL12) and that estrogens enhance susceptibility to experimental myasthenia gravis by augmenting dendritic cell activation and proinflammatory Th1 response (Delpy et al 2005, Douin-Echinard et al 2008. The pivotal role of estrogens in regulating dendritic cell differentiation and activation was also highlighted in other studies, in which E 2 was shown to support GM-CSF-initiated transition of bone marrow progenitor cells into dendritic cells, to prevent apoptosis, and to augment the production of proinflammatory and pro-atherogenic cytokines IL12 and IFNg by dendritic cells in response to TLR4 or TLR7 agonists (Carreras et al 2008, Kawasaki et al 2008, Siracusa et al 2008). The reasons why estrogens differentially affect macrophage and dendritic cell activation in vitro and in vivo and thereby exert dual effects on inflammation are currently unclear (see Straub (2007) for exhaustive discussion).…”
Section: Involvement Of Macrophages Dendritic Cells and Lymphocytesmentioning
confidence: 82%
“…The same group noticed that ERa-mediated signaling is required for optimal dendritic cell function as assessed by MHC-II and CD86 expression and pro-inflammatory cytokine production (IL6 and IL12) and that estrogens enhance susceptibility to experimental myasthenia gravis by augmenting dendritic cell activation and proinflammatory Th1 response (Delpy et al 2005, Douin-Echinard et al 2008. The pivotal role of estrogens in regulating dendritic cell differentiation and activation was also highlighted in other studies, in which E 2 was shown to support GM-CSF-initiated transition of bone marrow progenitor cells into dendritic cells, to prevent apoptosis, and to augment the production of proinflammatory and pro-atherogenic cytokines IL12 and IFNg by dendritic cells in response to TLR4 or TLR7 agonists (Carreras et al 2008, Kawasaki et al 2008, Siracusa et al 2008). The reasons why estrogens differentially affect macrophage and dendritic cell activation in vitro and in vivo and thereby exert dual effects on inflammation are currently unclear (see Straub (2007) for exhaustive discussion).…”
Section: Involvement Of Macrophages Dendritic Cells and Lymphocytesmentioning
confidence: 82%
“…This regulatory action of estrogens on immune responses and autoimmunity are thought to be due to a direct action on immunocompetent cells of the innate and adaptive immune systems (4), which have been recently shown to functionally express ERs, particularly ERa (5)(6)(7)(8)(9)(10)(11). Alternatively, estrogens, through their ERs, may act on precursor cells to regulate the differentiation and functions of lymphoid and myeloid cells (12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Several studies have shown a role for ERa signaling in the differentiation and functions of various DC subsets not only in vitro (13,(16)(17)(18), but also in vivo (11). DCs can be generated from bone marrow (BM) precursors cultured in the presence of GM-CSF or Flt3 ligand (Flt3L).…”
mentioning
confidence: 99%
“…However, the authors' used the DC properties of low buoyant density and adherence to glass to isolate and enrich for DCs (14). A variety of factors may influence the number of DCs in a tissue or animal at a given time, including infection, chronic disease states such as diabetes, hormones such as estradiol, nutrients such as vitamins A and D, as well as others (15)(16)(17)(18)(19)(20). However, previous methods used to analyze DCs have used enrichment techniques from pooled samples, either multiple tissue or animal sources, to obtain sufficient numbers of cells for analysis leading to potentially high variability and inaccurate DC number assessments.…”
mentioning
confidence: 99%